Strengthening Village Economies Through Cooperative Business Model Training - Widjaja, Hinijati (Edujavare Publishing, 2025)
This community service initiative aimed to strengthen rural economies by introducing and empowering local communities to adopt cooperative business models. Limited economic opportunities and fragmented individualistic approaches hinder sustainable development in many rural areas. This project sought to address these challenges by providing training on cooperative principles, governance, and practical business strategies. The method employed Participatory Rural Appraisal (PRA), engaging local participants in identifying community resources, challenges, and potential cooperative opportunities. Over three months, participants attended interactive workshops, field visits, and group discussions, leading to an increased understanding of cooperatives. The results demonstrated significant improvement in participants' knowledge, with a marked shift in mindset from individualistic to collective economic action. Several groups also began drafting cooperative bylaws and sought legal recognition for their ventures. While the initiative was successful, it highlighted the need for continuous support and follow-up to ensure long-term sustainability. The project contributes to rural development by demonstrating the potential of cooperatives as a tool for inclusive economic growth, emphasizing the importance of local ownership and community-driven solutions. Future initiatives should incorporate ongoing mentorship and involve local leaders more deeply in the facilitation process to ensure lasting impact.